PENGARUH PERMAINAN ESTAFET TERHADAP TINGKAT PERILAKU PROSOSIAL ANAK USIA 4-5 TAHUN DI TK ISLAM FATIMAH KECAMATAN TAMPAN KOTA PEKANBARU - Sianturi, Juli Ana; Chairilsyah, Daviq; Hukmi, Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to (1) to determine the level of prosocial behavior in children aged 4-5 years in Fatimah Islamic Kindergarten Tampan District, Pekanbaru City before the application of relay games (2) To determine the level of prosocial behavior in children aged 4-5 years in Fatimah Islamic Kindergarten Tampan Sub district, Pekanbaru City after the application of relay games (3) To determine the magnitude of the effect of relay play on prosocial behavior of 4-5 year old children in Fatimah Islamic Kindergarten, Tampan District, Pekanbaru City. The population in this study was 4-5 years of age at the Fatimah Islamic Kindergarten in Tampan District, Pekanbaru City. The sample in this study was group A totaling 15 children, consisting of 8 women and 7 men. Data collection used in this study was by pretest and posttest observation. The data analysis technique in this study used the t test using SPSS version 25. This research was an experimental study using the design of one group pretest posttest design. Based on the analysis of the data and the results of percentages on a significant effect, it can be seen from the results of the pretest (before treatment) obtained a value of 121 with an average of 8.07. Then do the experiment using relay games, so that the posttest obtained 192 values with an average of 12.8. To find out how much the influence of the relay game on the level of prosocial behavior of children used ideal scores where the use of relay games on the level of prosocial behavior of children aged 4-5 years in Islamic Fatimah Kindergarten in Tampan District, Pekanbaru City was 59.66 and 40.34% was influenced by other factors. Conclusion: with relay games can improve prosocial behavior of children aged 4-5 years in Fatimah Islamic Kindergarten Tampan District, Pekanbaru City.Key Words: Relay Games, Prosocial Behavior